Towards the Certification of Multicore Platforms in the Avionics Domain - Ali Awan, Muhammad (2015)
Presented at Work in Progress Session, The 28th GI/ITG International Conference on Architecture of Computing Systems (ARCS 2015). 24 to 27, Mar, 2015. Porto, Portugal.